Differentiation of Oil Production Break-even Level among World Oil Companies - Osintseva, Marina A. (International Journal of Energy Economics and Policy, 2021)
The issue of modern development in the oil industry has become extremely urgent. In 2020, for the first time in history, the exchange price of oil crossed the negative threshold, radically changing the understanding of economic processes in the industry. This paper examines the consequences of this stressful situation in the context of the financial stability of global oil companies in conjunction with ensuring the budgetary balance for resource-exporting countries. In the course of the study, the factors that influence the pricing in the oil market have been clarified. The authors have calculated break-even oil prices for the world's largest oil companies Saudi Aramco (SAU), ExxonMobil (USA), British Petroleum (GBR), and Rosneft (RUS). An analysis of the fiscal break-even of oil prices has shown that Russia, compared to the Gulf countries, has a greater margin of budgetary stability, since the break-even price of oil is several times lower than in Iran, Iraq, and Saudi Arabia. Based on the assessment of the operating leverage of the oil companies, a limit was set for the decline in profits as a result of the drop in oil production. The calculation of the target price for large global companies has shown that Rosneft has the highest price level due to high variable costs, and the target price for Saudi Aramco is approximately at the same level. ExxonMobil and BP's target price levels are lower. The results obtained confirm the need to continue searching for solutions to optimize costs to lower the breakeven level of oil production. Keywords: oil, break-even price, prime cost, pricing factors, budget balance, oil market, price shocks. JEL Classifications: L21, G31, Q49 DOI: https://doi.org/10.32479/ijeep.11260